Polyphenolic compounds and their supplementation in postmenopausal women - Połać, Ireneusz; Bobrowski, Mateusz; Bijak, Michał; Borowiecka, Marta; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2011)
Polyphenolic compounds are a broad group of organic compounds of plant secondary metabolites, which have in their structure one or more aromatic rings and from one to several hydroxyl groups with acidic character. Due to their heterogeneous construction polyphenolic compounds have been classified into several groups: simple phenols, phenolic acids, coumarins, xanthones, stilbenes, lignans, anthraquinones and the largest group – flavonoids. Polyphenols are characterized by a variety of biological activity. As natural antioxidants, they may protect against reactive oxygen species (ROS) and reactive nitrogen species (RNS). Moreover, they have the ability to seal blood vessels and of vasodilatation. Polyphenolic compounds also have anti allergic, antibiotic, antibacterial, antiviral, antifungal, anti-inflammatory and anticoagulation effects. Many recent studies have shown that a diet rich in polyphenolic compounds modulates several biomarkers of cardiovascular disease and cancer. Thanks to their pro-health properties, an increasing number of dietary supplements based on plant extracts are introduced for commercial use. Clinical studies confirm the effectiveness of supplementation with products containing polyphenolic compounds in the prevention of cardiovascular disease in postmenopausal women. Polyphenols also have the ability of aromatase inhibition, which means that they can be used in the prevention of breast cancer. This article describes the characteristics and biological properties of polyphenolic compounds, as well as clinical studies conducted in postmenopausal women taking polyphenols.